Practice-Based Education Perspectives and Strategies - Higgs, Joy.; Barnett, Ronald; Billett, Stephen; Hutchings, Maggie; Trede, Franziska; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
Practice-Based Education: Perspectives and Strategies. This book draws on the collective vision, research, scholarship and experience of leading academics in the field of practice-based and professional education. It presents multiple perspectives and critical appraisals on this significant trend in higher education and examines strategies for implementing this challenging and inspiring mode of learning, teaching and curriculum development. Eighteen chapters are presented across three sections of the book: Contesting and Contextualising Practice-Based Education Practice-Based Education Pedagogy and Strategies The Future of Practice-Based Education.
Keywords: Education; Education; Education, general; Electronic books